1999
DOI: 10.1300/j029v08n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Improving Initial Session Attendance of Substance Abusing and Conduct Disordered Adolescents: A Controlled Study

Abstract: The present controlled study was the first to demonstrate a method of improving first session attendance in a population of conduct disordered and substance abusing adolescents. The results indicated that an intensive intervention involving the youth and parent was more effective in improving session attendance than a less intensive intervention that excluded the youth's involvement. The intensive intervention resulted in greater attendance to the first appointment (60% vs. 89%), greater attendance to appointm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
0
44
1
Order By: Relevance
“…The CRAFT intervention was associated with a success rate for engaging resistant adolescents into treatment (i.e., 71%) that was similar to rates for CRAFT implemented with adult CSOs (Kirby et al, 1999;Meyers et al, 1999) and to rates for other adolescent engagement programs (Donohue et al, 1998). Once engaged, youth were retained in individual CBT, attending an average of two-thirds of the treatment sessions offered.…”
Section: Discussionmentioning
confidence: 79%
“…The CRAFT intervention was associated with a success rate for engaging resistant adolescents into treatment (i.e., 71%) that was similar to rates for CRAFT implemented with adult CSOs (Kirby et al, 1999;Meyers et al, 1999) and to rates for other adolescent engagement programs (Donohue et al, 1998). Once engaged, youth were retained in individual CBT, attending an average of two-thirds of the treatment sessions offered.…”
Section: Discussionmentioning
confidence: 79%
“…For example, the Health Belief Model (HBM, Rosenstock 1974) informed the interventions developed in a number of studies (e.g. Sawyer et al 2002;Watt et al, 2007;Donohue et al 1998;and McKay et al 1996a). The HBM proposes that health behavior depends on both an individual's perceptions of his/her vulnerability to an illness and his/her judgment of the perceived potential risk, barriers, or effectiveness of treatment (Elder et al 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, small effect sizes reveal that both interventions were not related to the perhaps more important ongoing use of services. Donohue et al (1998) compared two attendance interventions (Parent-focused attendance intervention vs. Intensive parent and youth attendance intervention) in a population of adolescents who were dually diagnosed with conduct disorder and substance abuse.…”
Section: Family Levelmentioning
confidence: 99%
“…Housing assistance, case management, regular phone contact, motivational interviewing and parental involvement for youth cases all decrease waiting list attrition. 2,20,21 In contrast, research also suggests that too many demands or requirements of patients during the waiting period is a deterrent for waiting. 8 In a pre-treatment survey, 16% of patients indicated that "I will have to go through too many steps to get into treatment" was a large barrier to entering treatment, along with the fact that they would have to be on a waiting list in the first place (34.3%).…”
Section: Why Patience Is Not Enoughmentioning
confidence: 99%
“…When patients are called by the facility every week, they are 30-40% more likely to enter treatment when compared to situations where the patient is responsible for maintaining contact. 21 In a study of 654 patients waiting for publicly funded drug treatment in Washington, D.C., 70% of patients successfully entered treatment when they were regularly contacted by telephone. 2 Donohue 21 suggests that reminder phone calls 2-3 days prior to patient's first appointment also produce 30-40% higher attendance rates when compared with patients who did not receive reminder phone calls.…”
Section: Initiate Weekly Phone Contactmentioning
confidence: 99%